The tourist imaginary in Costa Rica: from a “way of seeing” to “making a territory” - Linda Boukhris (Via@)
The representation of a peaceful state, without an army as well as the representation of wild nature are the two main constituents of Costa Rican tourist identity. The tourist imaginary is so powerful that it has led Costa Rica to become the top eco-tourism destination in the Central American ithmus. If this tourist imaginary is repsonsible for the creation of tourist sites, it is also involved in the construction of the territorial identity of Costa Rica by creating territorial symbols from which the national collective identification has taken shape. The tourist imaginary is not only a way of “seeing” the world but is “world-making”.